Where to leave a message? The selection and adaptive significance of scent-marking sites for Eurasian lynx - Allen, Maximilian L.; Hočevar, Lan; De Groot, Maarten; Krofel, Miha (Behavioral Ecology and Sociobiology, 2017)
Scent marking is an important aspect of social organization and intraspecific communication for many mammals, including solitary felids. By selecting specific micro-locations for scent marking, an individual may increase its success in defending its territory and finding mates. Few studies, however, have reported the selection of scent-marking objects and sites by wild felids. To improve our understanding of this behavior and its adaptive significance, we developed and tested a set of mutually non-exclusive hypotheses explaining selection of scent-marking objects by Eurasian lynx (Lynx lynx). We used snow tracking to locate and determine the characteristics of objects lynx used and selected for urine spraying. Lynx did not mark objects according to their availability but selected juvenile conifers and often marked the surface that was sheltered from the elements (%persistence hypothesis%). Lynx also selected for objects similar in size to lynx and objects located on straight road sections and avoided the most frequently available object types. This selection may have both promoted detectability of the messages by the conspecifics (%detection hypothesis%) and reduced energy expenditure of marking (%accessibility hypothesis%). Our study also indicated trade-offs faced by lynx, as the preferred marking objects were often not readily available. Therefore, suboptimal marking objects were sometimes used, most likely in order to maintain the high scent-marking frequency needed throughout their territory. We suggest that Eurasian lynx, and possibly other solitary felids, developed scent-marking behaviors that increase effectiveness and efficiency of their communication.